Voltage mirror circuit by carbon nanotube field effect transistors for mirroring dynamic random access memories in multiple‐valued logic and fuzzy logic. Issue 5 (1st September 2015) - Jasemi, Masoomeh; Faghih Mirzaee, Reza; Navi, Keivan; Bagherzadeh, Nader
Abstract : In this paper, a new voltage mirror circuit by using carbon nanotubes (CNTs) technology is presented. This circuit is specifically proposed for the application of duplicating multiple‐valued and fuzzy dynamic random access memories. The given structure prevents any voltage drop for the capacitor inside the memory cell. As a result, any fanout circuit can be driven. The new structure can be utilised for different multiple‐valued logic systems without a change. The unique characteristics of carbon nanotube field effect transistor (CNFET) technology are exploited in this paper to meet the desired design goals. It demonstrates the potentials of CNFET technology in a realistic very large‐scale integration application. The proposed design is highly tolerant to D CNT variation and it is also immune to misaligned CNTs. Simulation results demonstrate that it provides sufficient driving capability with reasonable accuracy.